Analysis of the Influence of Work Environment and Work Competence on Employee Performance: The Mediating Role of Work Motivation - Bela Safitri; Ratna Kusumawati (Faculty of Economics and Business, Universitas Wahid Hasyim, 2026)
This study aims to analyze the effects of the work environment and work competence on employee performance, with work motivation as a mediating variable. This study uses a quantitative approach, with the sample size is 88 employees, determined by a sampling technique based on research criteria at the regional secretariat office of Central Java Province. The data analysis method used is path analysis to determine both direct and indirect effects among variables. The results of the study indicate that the work environment has a positive and significant effect on employee performance. Work competence also has a positive and significant effect on employee performance. Meanwhile, the mediation test results indicate that work motivation mediates the effect of the work environment on employee performance. However, work motivation does not mediate the effect of work competence on employee performance. This indicates that the influence of the work environment on employee performance can be strengthened by increased work motivation. In contrast, the effect of work competence on employee performance is more directly dominant, without going through a mediating variable. Thus, it can be concluded that the improvement of employee performance at the regional secretariat office of Central Java Province is influenced by the work environment and work competence, where work motivation acts as a mediating variable in the relationship between the work environment and employee performance, but not in the relationship between work competence and employee performance.